2010
DOI: 10.1111/j.1537-2995.2010.02588.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Canadian Blood Services donors for severe immunoglobulin A deficiency

Abstract: Results from the ARC confirmed a frequency of 1 in 546 in the CBS' blood donor population for severe IgA deficiency (<0.05 mg/dL), 1 in 840 for those without anti-IgA, and 1 in 1560 for those with antibody. Donors repeatedly confirmed as severely IgA deficient without anti-IgA were considered eligible for the CBS IgA-deficient donor registry program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…In addition, many registries of blood donors with IgA deficiency have been established in different countries [4,5,6]. Nevertheless, anaphylactic reactions due to anti-IgA cannot invariably be prevented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many registries of blood donors with IgA deficiency have been established in different countries [4,5,6]. Nevertheless, anaphylactic reactions due to anti-IgA cannot invariably be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that such reactions can be prevented by providing IgA-deficient blood components collected from IgA-deficient blood donors. Based on this option, registries of such donors have been established in the USA, Canada, and some countries in Europe and Asia [4,5,6,7]. However, in practice, the use of these rare products cannot be realized in many instances, particularly in emergencies or where platelets are required [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 54 594 Canadian blood donations were screened for serum IgA levels and the prevalence of IgAD was 1 : 219 [22], which is higher than the prevalence reported previously in Whites [8]. In 2011, 22 609 healthy Chinese blood donors were also screened for IgA levels and 14 of them were shown to be IgAD, giving a prevalence of 1 : 1615 [23], markedly higher than that previously reported in China (1 : 4100) [24], suggesting that the prevalence of IgAD is probably slightly undervalued in the Chinese population.…”
Section: Clinical Picturementioning
confidence: 99%
“…However, the worldwide prevalence varies, and reported figures vary within the same population depending on the method of immunoglobulin measurement and cutoff values used (Latiff and Kerr, 2007;Feng et al, 2011). The prevalence may be as high as 1/188 in Turkey (Baştürk et al, 2011) or 1/219 in Canada (Palmer et al, 2010), or as low as 1/4100 in China (Feng et al, 2011) or 1/31,800 to 1/23,255 in Japan (Kanoh et al, 1986;Ozawa et al, 1986). The low prevalence in the Chinese and Japanese populations strongly suggests a genetic influence on the development of the disease.…”
mentioning
confidence: 94%
“…The low prevalence in the Chinese and Japanese populations strongly suggests a genetic influence on the development of the disease. For more detailed figures relating to the prevalence of IgAD in different populations, the reader is advised to refer to Mestecky and Hammarström (2007), Weber-Mzell et al (2004), and Palmer et al (2010).…”
mentioning
confidence: 99%